UJI AKTIVITAS PESTISIDA NABATI SECARA IN VITRO - Mokhamad Irfan (Jurnal Agroteknologi, 2010)
Biopesticide materials extracted from union, mimba leafs, peper betle leafs, lemon grass, and comercial bactericide as control. Bacteria soruces by isolation from rotten cabbage and pineapple. Medium composition of nutrien agar are vitabro 1 g/L, vitamineral 4 g/L, sucrose 7 g/L, skim milk 2 g/L, and agar 11 g/L, whereas broth composition is not added agar. Pure microbial was made by strep method. Inhibition zone of antimicrobe was measured by formula in mm2. Isolation result from rotten cabbage are four coccus bacteria and one bacil bacteria with four positives and one negative gram bacteria. Isolate bacteria from pineapple were one negative and one positive gram. Union extraction had antimicrobe activitiy highest (average 1200 mm2) than others biopesticide. Union extraction had inhibits of growth to all bacteria, bacil, coccus, positive and negative gram. Meanushile peper betle leafs only had antimicrobe activity for coccus negative gram. Boiling on biopesticide sources at 1000C for 45 second could decreasing of antimicrobe activity but fermentation process increased of antimicrobeial activity. Fermentation was increasing of inhibition zone peper betle leafs at 8.6 mm2 on bacil positive gram bacteria, 8.6 mm2 on bacil positive gram, and 30.6 mm2 on coccus negative gram bacteria. Decrease of union activity was estimated by dilution at fermentation.